2019
DOI: 10.3390/v11030207
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature and Low UV Indexes Correlated with Peaks of Influenza Virus Activity in Northern Europe during 2010–2018

Abstract: With the increasing pace of global warming, it is important to understand the role of meteorological factors in influenza virus (IV) epidemics. In this study, we investigated the impact of temperature, UV index, humidity, wind speed, atmospheric pressure, and precipitation on IV activity in Norway, Sweden, Finland, Estonia, Latvia and Lithuania during 2010–2018. Both correlation and machine learning analyses revealed that low temperature and UV indexes were the most predictive meteorological factors for IV epi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 21 publications
6
47
0
3
Order By: Relevance
“…We showed that >10 sec of UVC radiation or 48 h incubation at 37 °C neutralized SARS-CoV-2, establishing a rationale and methodology for safe work in the laboratory. These results are consistent with previous studies showing that physical factors destabilize SARS-CoV-2 and other viruses (Cadnum et al, 2020;Demongeot et al, 2020;Ianevski et al, 2019b;Sobral et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…We showed that >10 sec of UVC radiation or 48 h incubation at 37 °C neutralized SARS-CoV-2, establishing a rationale and methodology for safe work in the laboratory. These results are consistent with previous studies showing that physical factors destabilize SARS-CoV-2 and other viruses (Cadnum et al, 2020;Demongeot et al, 2020;Ianevski et al, 2019b;Sobral et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…The complex relationship between temperature and solar radiation, as shown in Figure 2, is important, because the effects of temperature and light, particularly in the ultra-violet spectrum, have been shown to be associated with seasonal viral activity in other contexts. [11] In this assessment, the independent association of precipitation with COVID-19 incidence rates was also appreciable. A recent meteorological analysis showed very similar weather patterns across a number of COVID-19 hotspots, including Wuhan City, in a corridor 30° to 50° North in early 2020.…”
Section: Discussionmentioning
confidence: 66%
“…Conversely, brighter, drier weather may stimulate levels of social interaction, and thereby possibly counteract direct effects of heat and light on viruses. The complex observed relationship between temperature and solar radiation, as shown in Figure 2, is important, because the effects of temperature and light, particularly in the ultra-violet spectrum, have been shown to be associated with seasonal viral activity in other contexts [17]. In this assessment, the independent association of precipitation with COVID-19 incidence rates was also appreciable.…”
Section: Discussionmentioning
confidence: 80%